ANKARA İLİ KEÇİÖREN İLÇESİNDE YAŞAYAN CAFERİLERDE DİNİ HAYAT VE İLÇENİN GÜNÜMÜZ DİNİ DURUMU - DAĞDEVİREN, ERCAN (Fırat Üniveristesi, 1998)
The Keçiören Town's population is increasing day by day because of the migration from the cities such as; Çorum, Yozgat, Kırşehir, Çankırı. At the end of the study we had done, we didn't witness any non-Moslem person. All the population living in Keçiören, 733.488, are Moslems. The Caferiler who live in Keçiören only consist 1500 people of the population. Caferiler imigrated to Keçiören from Kars and İğdır. İh order to keep their sect and transfer it to the next generation Keçiören Alawis built two mosques different from the divotion's ones and they appointed two imams who had their education in Iran and whose salaries have been paid by their religious education in those mosques. All Alawis have their ceremonies on holy days and nigts in their mosques. There have been devotion Critiques among the Alawis and Caferi who live in Keçiören. Those who belong to the group of Caferi blame the Alawis for not obeying the Holy Book Kur' an and its Sunna and they think that those who leave from twelve Imam's principals can't be real Alawis. Two big groups are seen in the religion structure of the town. Hanefis consist 71 vercent of the population with 733.448 people, and Alawis consist 29 percent of the population. Alawis migrated to Keçiören from Tunceli, Kars, Çorum, Çankırı, Yozgat and they dwell in Ovacık, Şenyuva, Esentepe, 19 Mayıs, Yayla, Kuşcağız quarters of the town. Among the present sects Erenköy, İskenderpaşa and Adıyaman Menzil groups belong to the Nakşibendi sect. Among Kadris Haydar Baş' s group draw attention. Among the attendance Fethullah Hodja'c group show activity in houses and another group show activities in student's education hostels in Hasköy quarter. 60
The Living Ankara`s Keçiören town which the caferis religion living and its condition
Bu tezin, veri tabanı üzerinden yayınlanma izni bulunmamaktadır. Yayınlanma izni olmayan tezlerin basılı kopyalarına Üniversite kütüphaneniz aracılığıyla (TÜBESS üzerinden) erişebilirsiniz.
Keywords: Din; Religion